2014
DOI: 10.7314/apjcp.2014.15.5.1909
|View full text |Cite
|
Sign up to set email alerts
|

miR-421, miR-155 and miR-650: Emerging Trends of Regulation of Cancer and Apoptosis

Abstract: It is becoming progressively more understandable that between transcription and translation there lies another versatile regulator that quantitatively controls the expression of mRNAs. Identification of miRNAs as key regulators of wide ranging signaling cascades and modulators of different cell-type and context dependent activities attracted basic and clinical scientists to study modes and mechanisms in details. In line with this approach overwhelmingly increasing in vivo and in vitro studies are deepening our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…The present study observed that the phosphorylation levels of AKT and ERK representative of signaling pathway activation decreased subsequent to miR-155 silencing, but it has yet to be determined whether the mechanism involves the regulation of PTEN expression. However, it has been revealed that the role of miR-155 in tumors involves multiple aspects and miR-155 interacts with the intracellular transcription factors regulating gene transcription (42,43). The present results demonstrated the ability of miR-155 to positively regulate the activity of NF-κB and AP-1.…”
Section: A B C D E Fsupporting
confidence: 54%
“…The present study observed that the phosphorylation levels of AKT and ERK representative of signaling pathway activation decreased subsequent to miR-155 silencing, but it has yet to be determined whether the mechanism involves the regulation of PTEN expression. However, it has been revealed that the role of miR-155 in tumors involves multiple aspects and miR-155 interacts with the intracellular transcription factors regulating gene transcription (42,43). The present results demonstrated the ability of miR-155 to positively regulate the activity of NF-κB and AP-1.…”
Section: A B C D E Fsupporting
confidence: 54%
“…Each miRNA is predicted to have hundreds of mRNA targets caused by the imperfect base pairing (Lim et al, 2005) to the 3' untranslated region (UTR) of the target mRNAs and signalling the target for mRNA degradation. Thus, miRNAs have been identified as performing significant regulatory functions in various cellular, biological and pathological processes, including the differentiation, progression, apoptosis, and proliferation of cancer cells (Heneghan et al, 2010;Farooqi et al, 2014). These molecules characteristically moderate the translation and stability of mRNAs, including those genes that mediate processes in carcinogenesis, including the immune response, metabolism, inflammation, cell cycle control, viral replication, stem cell differentiation and human development (Farazi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have been extensively studied regulators in molecular oncology and it is now evident that tumor suppressor miRNAs are repressed/downregulated and oncogenic miRNAs are overexpressed in cancer cells (Farooqi et al, 2014;Mollaie et al, 2013;Orang et al, 2014). Differential expression of miRNAs has been studied in different cancers and high-throughput technologies have added new layers of information into the existing pool of knowledge (Ding et al, 2014;Diao et al, 2014).…”
Section: Mirna Response Element Controlled Expression Of Trailmentioning
confidence: 99%